Cross-Cultural Differences in the Generation of Novel Ideas in Middle Childhood - Köster, Moritz; Yovsi, Relindis; Kärtner, Joscha (Frontiers in Psychology, 2020)
Innovation and creativity have recently been in the center of the debate on human cultural evolution. Yet, we know very little about childrens’ developing capacity to generate novel ideas, as a key component of innovation and creativity, in different cultural contexts. Here we assessed 8- to 9-year-old children from an autonomous and a relational cultural context, namely Münster (urban Germany; n = 29) and Banten (rural Cameroon; n = 29). These cultural contexts vary largely in their ecology, social structure, and educational system, as well as the cultural models on children’s individual development and thinking. Therefore, they provide an optimal contrast to investigate cultural similarities and differences in devepolment of creative capacities. We applied a classical divergent thinking tasks, namely an alternative uses task and a pattern association task. In these tasks, children are asked to generate as many ideas as possible what an object could be used for or what a pattern could be. First, our study revealed a good internal consistency and inter-task correlations for the assessment of children’s fluency and the generation of unique ideas in both cultures. Second, and most critically, we found significantly higher levels of creative capacities in children from Münster in contrast to Banten. This was reflected in both a higher number of ideas (fluency) and a higher number of unique ideas (uniqueness). Third, looking at the type of answers that children gave in the alternative uses task, we found that children from Münster and Banten uttered a similar number of conventional ideas, but that children from Münster uttered more ideas to manipulate an object, invent novel things with an object, involve an object in play or pretend play, or in a fantasy story. This demonstrates that early creative development is strongly influenced by the cultural context and substantiates the cultural nature of human cognitive development.